Intractable hiccup and nausea in neuromyelitis optica with anti-aquaporin-4 antibody: a herald of acute exacerbations. Issue 9 (17th April 2008) - Takahashi, T; Miyazawa, I; Misu, T; Takano, R; Nakashima, I; Fujihara, K; Tobita, M; Itoyama, Y
Abstract : Background: Intractable hiccup and nausea (IHN) are unique symptoms in neuromyelitis optica (NMO). Recent studies have strongly suggested that the pathogenesis of NMO is closely associated with anti-aquaporin-4 (AQP4) antibody. However, clinical implications of IHN and the relationship with anti-AQP4 antibody remain unknown. Methods: The past medical records of 35 patients with seropositivity for anti-AQP4 antibody were reviewed. We also followed the titres of anti-AQP4 antibody in a patient with NMO, who had newly developed IHN. Results: Of the 35 patients, 15 patients (43%) had episodes of IHN. There was a total of 35 episodes of IHN in these 15 patients and, of the 35 episodes, hiccup was seen in 23 episodes (66%) and nausea was seen in 28 episodes (80%). The IHN frequently preceded (54%) or accompanied (29%) myelitis or optic neuritis. The IHN was often preceded by an episode of viral infection. The titres of anti-AQP4 antibody were remarkably increased when the intractable hiccup appeared in a case. Conclusions: IHN could be a clinical marker for the early phase of an exacerbation. Careful observation may be needed when INH is seen in patients with NMO, and the early initiation of the treatment could prevent subsequent neurological damage.